Diverse Modes of Reactivity of 6‐(Chloromethyl)‐6‐methylfulvene. Issue 20 (29th May 2017) - Erden, Ihsan; Gronert, Scott; Cabrera, Gabriel; Coskun, Necdet; Tapken, Marco
Abstract : The title compound exhibits a number of modes of reactivity toward nucleophiles/bases owing to the presence of several electrophilic and potentially nucleophilic sites in the molecule. We explored the reactions of 6‐(chloromethyl)‐6‐methylfulvene with oxygen and nitrogen nucleophiles and bases as well as a carbon‐based nucleophile (an enamine) and realized all possible reactivity modes predicted on the basis of electrophilic and nucleophilic positions in this compound. Abstract : 6‐(Chloromethyl)‐6‐methylfulvene is an exceptionally reactive compound toward a variety of nueclophiles. Alkoxides attack the exocyclic double bond (C‐6) to initially give spiro[2.4]heptadiene intermediates which ring‐open to cyclopentadienyl anions. The latter can be trapped in fulvene‐forming condensations. We also observed an unprecedented aldol condensation at the CH2 Cl group as well as [6+2] dipolar cycloadditions.